Bone-Targeting Endogenous Secretory Receptor for Advanced Glycation End Products Rescues Rheumatoid Arthritis - Tatsuo Takahashi; Sayaka Katsuta; Yusuke Tamura; Nozomi Nagase; Keita Suzuki; Masaaki Nomura; Shunji Tomatsu; Ken-ichi Miyamoto; Shinjiro Kobayashi (BMC, 2013)
Abstract Rheumatoid arthritis (RA) is a chronic inflammatory synovitis that leads to the destruction of bone and cartilage. The receptor for advanced glycation end products (RAGE) is a multiligand membrane-bound receptor for high-mobility group box-1 (HMGB1) associated with development of RA by inducing production of proinflammatory cytokines such as tumor necrosis factor (TNF)-α, interleukin (IL)-1 and IL-6. We developed a bone-targeting therapeutic agent by tagging acidic oligopeptide to a nonmem-brane-bound form of RAGE (endogenous secretory RAGE [esRAGE]) functioning as a decoy receptor. We assessed its tissue distribution and therapeutic effectiveness in a murine model of collagen-induced arthritis (CIA). Acidic oligopeptide-tagged esRAGE (D6-esRAGE) was localized to mineralized region in bone, resulting in the prolonged retention of more than 1 wk. Weekly administration of D6-esRAGE with a dose of 1 mg/kg to RA model mice significantly ameliorated inflammatory arthritis, synovial hyperplasia, cartilage destruction and bone destruction, while untagged esRAGE showed little effectiveness. Moreover, D6-esRAGE reduced plasma levels of proinflammatory cytokines including TNF-α, IL-1 and IL-6, while esRAGE reduced the levels of IL-1 and IL-6 to a lesser extent, suggesting that production of IL-1 and IL-6 reduced along the blockade of HMGB1 receptor downstream signals by D6-esRAGE could be attributed to remission of CIA. These findings indicate that D6-esRAGE enhances drug delivery to bone, leading to rescue of clinical and pathological lesions in murine CIA.